Potential of solar photovoltaic façade on lecturer building facility - Rishal Asri; Koko Friansa; Guna Bangun Persada (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2019)
Lecturer Building is a facility that has full of activity and full of people inside from morning until afternoon. The Lecturer Building use in this research has a big problem with electricity utility which the energy source of the building until now still using limited fossil energy in its use. Another problem with the façade building was facing the sun in the morning. Then the temperature building was increasing and make uncomfortable conditions inside. Window integrated Solar PV or solar façade not only reducing incoming solar radiation but generate electricity.